Prevalence of canine parvoviral enteritis in pet dogs at Dhaka city of Bangladesh - Roy, Sawrab; Ahmed, Juned; Basit, Md. Shamsul Islam; Ahmed, Sagir Uddin; Alam, Shahrul; Chowdhury, Q M Monzur Kader; Sharma, Binayok; Rahman, Mohammad Sujaur; Popy, Farzana Yeasmin (International Journal of Biological Research, 2018)
Background: Canine parvoviral enteritis is a highly contagious viral disease of dog that can lead to life-threating illness.Objectives: The present study was conducted to determine the prevalence of canine parvoviral enteritis in dogs of Dhaka City Corporation, Bangladesh.Methods: A total of 545 dogs were examined at Dr. Sagir’s Pet Clinics and Research Centre, Dhaka during September 2016 to August 2017. The disease was diagnosed on the basis of clinical history, clinical signs and by CPV rapid Ag kit test.Results: Overall prevalence of canine parvoviral enteritis was recorded as 13.94%. The prevalence of canine parvoviral enteritis varied significantly (p<0.05) among different aged groups (23.63%, 10.63%, 8.27% in 0-6 months, 7-12 months and above 12 months respectively). Considering seasonal influences, highest prevalence was found in summer season (17.5%) followed by winter (12.12%) and rainy season (11.66%) which was statistically insignificant (p>0.05). Male dogs (18.74%) were found to be significantly (p<0.05) higher susceptible in comparison with female (11.00%).Non-vaccinated dogs (80.0%) were at greater risk than vaccinated (2.58%), (p<0.05). There was significant (p<0.05) difference among various breeds where German Shepherd (40.78%) had highest prevalence of canine parvoviral enteritis followed by Labrador (22.36%), Rottweiler (21.05%), Doberman (13.15%) and cross breeds (4.4%). Dogs with poor health condition (20.75%) were more vulnerable than apparently healthy dogs (7.5%), (p<0.05).Conclusion: This result provides an empirical scenario of canine parvoviral enteritis in Dhaka city. Effective routine vaccination and control measures may reduce the disease burden in dog population.